Improving Engineering Studentsʼ Understanding of Components of Cyber-Physical Systems Using a Team Project-Based Teaching Method - A. A. Charyyeva; S. M. Nokerov; P. E. Hojagulyyev; A. M. Orazov; A. P. Venkataraman; Th. Bikku (Цифровая трансформация)
This article describes a teaching method that was used to teach second-year mechatronics and robotics students the components of cyber-physical systems. In view of the importance of team learning, the group was divided into five sub-groups (student teams) in order to increase efficiency by comparing the tasks undertaken by the teams. A line following robot was used for the teaching. This course was designed to last 48 academic hours. As a result, the students noted that after building the robot in teams, their attitude towards cyber-physical systems changed, and they became motivated to carry out larger projects related to cyber-physical systems.